Մկրտիչ Խէրանեանը՝ Գրիգոր Նարեկացու «Մատեան ողբերգութեան» երկի թարգմանիչ - Ապրեսեան, Անուշ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье рассматривается один из важнейших переводов «Книги скорбных песнопений» Григора Нарекаци с грабара на новоярмянский язык. На примере перевода Мкртыча Хераняна предпринимается попытка изучить, как переводчик воспринимает, интерпретирует и воспроизводет на современном армянском средневековое произведение, с какими проблемами сталкива- ется при переводе и какие методы их решения использует. Изучение данного перевода не только предоставляет возможность оценить труд переводчика, но и выявить проблемы и особенности перевода, которые в дальнейшем могут способствовать появлению новых, более совершенных переводов «Книги скорбных песнопений». Мкртыч Херанян создал перевод, благодаря которому восточноармянский читатель знакомится с «Книги скорбных песнопений» даже через тысячу лет. Несмотря на некоторые упущения и разнообразные переводы, в большинстве примеров Хераняну удалось сохранить стихотворный размер, ритмика, рифма, ритм и лексику оригинального текста. В тех случаях, когда черты оригинала не сохранились, они иногда были обусловлены чертами древнеармянского азыка, а иногда — стилем переводчика. The article considers one of the important translations of the Book of Lamentations by Gregory of Narek from the Classical Armenian into Modern Armenian language. On the example of Mkrtich Kheranyan’s translation, an attempt is made to study how the translator perceives, interprets and reproduces the medieval work in Modern Armenian, what problems he faces while translating the text and what solutions he offers. The analysis of this translation not only provides an opportunity to evaluate the translator’s efforts, but also detects problems and some peculiarities of the translation, which in the future can contribute to the emergence of new, improved translations of the Book of Lamentations. Thanks to Mkrtich Kheranyan’s translation, Eastern Armenian readers can get acquainted with the Book of Lamentations even after a thousand years. However, despite some omissions and various translations, in most of the examples Kheranyan managed to preserve the prosody, the rhyme, the rhythm and vocabulary of the original text. The cases, in which features of the original are not preserved, are sometimes conditioned by the traits of the Classical Armenian language, and sometimes—by the style of the translator.
Keywords: Գրախօսութիւն